The impacts of poverty on hunger: An examination of the relationship between socioeconomic status and food insecurity - Upasana Singh (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2023)
Hunger is a persistent global problem affecting billions of people worldwide, particularly those living in poverty and developing countries. Research work relates to experimental research work on the causes and effects of hunger and proposes potential solutions to address the problem. Poverty, conflict, natural disasters, climate change, and gender inequality are major drivers of hunger. Hunger leads to malnutrition, which impairs physical and cognitive development, reduces economic productivity, and undermines social stability. Addressing the underlying causes of hunger through policies that promote economic growth, sustainable agriculture, access to education and healthcare, social protection programs, and conflict resolution can create a world where everyone has access to adequate and nutritious food. By implementing a comprehensive and integrated approach, we can reduce hunger and ensure that it is no longer a barrier to economic and social development. This research was done to find out the solution to this issue. In the research work, I have studied data and analyzed it for the solutions. I have tried to present all the above concepts in a lucid way so as present the related concept in an effective manner.